Combining hydrodynamics, hydrochemistry, and environmental isotopes to understand the hydrogeological functioning of evaporite-karst springs. An example from southern Spain - Gil-Márquez, José Manuel; Andreo-Navarro, Bartolomé; Mudarra-Martínez, Matías (Elsevier, 2019)
This work adopts a multicriteria approach to investigate the functioning of evaporite-karst systems, rarely studied. The natural responses of the main discharge point of the system of study (Lower Anzur spring) were controlled by continuous monitoring of the discharge rate, water temperature, and electrical conductivity. Water samples were collected for chemical analysis and the determination of intrinsic fluorescence, stable isotopes (δ18O, δ2H) and tritium (3H) concentrations. Physico-chemical data were examined applying principal component analysis (PCA) and trend analysis tests (Mann-Kendall and Sen’s slope). The system shows a clear karstic functioning, highly dependent on concentrated recharge, but with a limited drainage capacity of the conduit network. The piston-flow effects at the beginning of floods indicate a contribution to the drainage of deep ascending flows. Subsequent drops in temperature and mineralization in the water drained by the spring, as well as a recent infiltration deduced from the signature of intrinsic fluorescence and stable isotopes, point to a good hydrogeological connection with the recharge areas. Quick restoration of the initial values of mineralization reveals a fast geochemical evolution of the recently infiltrated groundwater, which may be a distinctive trait of evaporite karst aquifers. Lastly, the high solute content of the spring water in depletion conditions, with ascending trends of mineralization and temperature observed during several dry years as a consequence of lower recharge contribution, together with the tritium data, suggest the existence of an old component partly responsible for the spring base flow. Thus, groundwater would be linked to gravity-driven regional flows, but also to recent conduit flows. All the results obtained led us to devise a hydrogeological conceptual model and the results presented here demonstrate the advantages of using diverse techniques when investigating evaporite karst aquifers.
Keywords: Procesos hidrogeoquímicos; Evaporite karst; Hydrogeochemical processes; Hydrodynamics; Tritium; S Spain